Teaching package improves mothers knowledge on vaccine preventable diseases and vaccination: a Quasi experimental study - V, Prathibha D’Souza; J, Umarani (International Journal of Research in Medical Sciences, 2017)
Background: Today vaccination is a very essential part of child’s health. Vaccination programme is the key step for the vaccine preventable diseases in children. Objectives of current study were 1. To assess the knowledge of mothers regarding selected vaccine preventable diseases and vaccination. 2. To find the effectiveness of teaching package on knowledge regarding selected vaccine preventable diseases and vaccination among mothers. 3. To find the association between pre-test knowledge score and demographic variables. Methods: An evaluative approach with quasi experimental - Two group pre-test and post-test design was adopted. The sample comprised of 100 mothers in selected hospitals of Mangalore who were selected by purposive sampling technique and assigned to control and experimental group. On first day pre-test was conducted with a structured knowledge questionnaire to both control and experimental group and teaching package was given only to the experimental group followed by post-test and information booklet to both the groups on 7th day. Results: The mean and standard deviation of post-test knowledge score of mothers in experimental group (27.80 ± 3.010) was much greater than pre-test value (10.44 ± 2.323). There is no change in pre and post-test knowledge score in control group (9.74 ± 1.805). The calculated’ value t98=34.54 was greater than the table value 1.68 at 0.05 level of significance. This indicates that the teaching package was effective in improving the level of mothers knowledge. Conclusion: The study findings concluded that the mothers were benefited by teaching package on vaccination and vaccine preventable diseases. Furthermore mass health education programs can be conducted to create awareness among general public.